Optimising micronutrient-driven productivity in groundnut through foliar boron for a climate-resilient oilseed farming strategy - Suresh, KBT; Sivakumar, K; Jeyajothi, R; Chandrasekaran, P; Vasanth, P; Mohammed, A A (Plant Science Today, 2026)
Micronutrient limitations continue to constrain the economic potential of groundnut production, particularly in nutrient-responsive soils where biological nitrogen fixation and reproductive processes impose high physiological demands. This study aimed to test the hypothesis that targeted foliar application of boron or molybdenum, in combination with recommended macronutrient fertilisation, can substantially enhance both the biophysical performance and economic viability of groundnut cultivation. A field assessment was conducted using 9 nutrient-management treatments involving soil and foliar routes of boron and molybdenum under full and reduced nutrient regimes. Instead of detailing stage-wise biometric responses, the findings are synthesised to highlight key technological and economic outcomes. Foliar boron at 0.5 % with 100 % recommended nutrient dose emerged as the most productive and cost-efficient strategy, increasing pod yield, enhancing photosynthetic performance, strengthening nodulation efficiency and generating the highest net returns. The interdisciplinary significance lies in connecting plant nutrition physiology with farm-level profitability metrics, revealing new opportunities for resource-efficient fertilization practices. These results demonstrate that a simple micronutrient-based intervention can support climate-resilient production, reduce hidden nutrient losses and create financially attractive pathways for oilseed farmers and agri-input stakeholders. Prospective research directions include scaling this approach through digital decision-support tools, micronutrient blending technologies and region-specific cost–benefit simulations.